When Protection Becomes Exploitation: The Impact of Firing Costs on Present-Biased Employees - Florian Englmaier; Matthias Fahn; Ulrich Glogowsky; Marco A. Schwarz (Center for Economic Studies and ifo Institute (CESifo), 2023)
Employment protection harms early-career employees without benefitting them in later career stages (Leonardi and Pica, 2013). We demonstrate that this pattern can result from employers exploiting naïve present-biased employees. Employers offer a dynamic contract with low early-career wages, an unattractive intermediate qualification stage, and high end-of-career wages. Upon reaching the qualification stage, present-biased employees exchange future wages for immediate rewards on an alternative career path – a choice unanticipated by their previous, naïve, self. Thus, employers never pay high future wages. Firing costs help employers indicate that they will not oust employees instead of making promised payments, enabling early-career wage cuts.
Keywords: D21; D90; J33; K31; M52; 330; employment protection laws; present bias; dynamic contracting